Allan Boesak: innocence and the struggle for humanity - M. Cloete (Acta Theologica)
As a Black theologian and political activist, deeply committed to the cause of freedom, reconciliation and justice in South Africa, Allan Boesak has embraced the philosophy of Black consciousness as a legitimate moral-political foundation for the development of national unity. Boesak is of the view that post-apartheid South Africa is still deeply plagued by a racist legacy of moral-political “innocence”. I explore the validity of Boesak’s position from the perspective of his fundamental claim that the philosophy of Black Consciousness represents a legitimate framework for addressing the legacy of “innocence”, construed by him as an epistemic condition that refuses to engage with the historical “truth” of race thinking.